2024
DOI: 10.1186/s40538-024-00549-1
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial inoculants and enzymes based silage cocktails boost the ensiling quality of biomasses from reed, corn and rice straw

Evan Y. Liu,
Shuiping Wang,
Shibo Wang
et al.

Abstract: This study investigated the effects of bacterial inoculants and enzyme-based silage cocktails on the dynamics of fermentation, microbiome, and nutritional value of silages produced from low-quality biomasses of reed, rice, and corn straw. A 90-day ensiling trial was performed using five distinct combinations of six basal bacterial species (Lactobacillus plantarum, Lactobacillus buchneri, Pediococcus pentosaceus, Aspergillus niger, Bacillus subtilis, and Candida utilis) and three basal enzymes (xylanase, β-mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Further studies are suggested with more treatment periods (like obtaining data on a weekly basis) and involving other factors like increasing the amount of inoculum, optimizing the chop size of the substrate and supplementing essential nutrients for a more precise optimization for the treatment period and the nutritional upgradation of SCB using WRF. The extraction and application of bacterial and fungal ligninolytic enzymes can also be used to improve the degradability of LCB [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are suggested with more treatment periods (like obtaining data on a weekly basis) and involving other factors like increasing the amount of inoculum, optimizing the chop size of the substrate and supplementing essential nutrients for a more precise optimization for the treatment period and the nutritional upgradation of SCB using WRF. The extraction and application of bacterial and fungal ligninolytic enzymes can also be used to improve the degradability of LCB [48,49].…”
Section: Discussionmentioning
confidence: 99%